Ultra-broadband two-pump optical parametric amplifier in tellurite waveguides with engineered dispersion - Marconi, Jorge D.; Abbade, Marcelo L. F. [UNESP]; Serpa-Imbett, Claudia M.; Fagotto, Eric A. M. (Optica Publishing Group, 2017)
The capacity of communication networks may be significantly improved by simply enhancing the optical amplifier bandwidth. This paper presents a numerical investigation of an ultra-broadband, low-ripple, two-pump-optical parametric amplifier (2P-OPA) that employs a tellurite glass buried-channel type nano-waveguide as nonlinear medium. The nano-waveguide was designed as a 25-cm-long Archimedean spiral that occupies a footprint of only ∼2.5 mm2, with a ∼0.7 μm2 effective cross section. Its zero-dispersion wavelength is ∼1550 nm, the nonlinear coefficient is ∼3000 W-1 km-1, and the attenuation coefficient is ∼0.5 dB/m (1100 to 1900 nm). Simulations suggest a 2P-OPA based on such waveguide will be able to amplify 243 QPSK input channels modulated at 56 Gbps over 102 nm bandwidth, over metropolitan area network scales.